2020
DOI: 10.1007/s00401-020-02207-w
|View full text |Cite|
|
Sign up to set email alerts
|

Antibody against TDP-43 phosphorylated at serine 375 suggests conformational differences of TDP-43 aggregates among FTLD–TDP subtypes

Abstract: Aggregation of hyperphosphorylated TDP-43 is the hallmark pathological feature of the most common molecular form of frontotemporal lobar degeneration (FTLD–TDP) and in the vast majority of cases with amyotrophic lateral sclerosis (ALS–TDP). However, most of the specific phosphorylation sites remain to be determined, and their relevance regarding pathogenicity and clinical and pathological phenotypic diversity in FTLD–TDP and ALS–TDP remains to be identified. Here, we generated a novel antibody raised against T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…One of the features of ALS and FTLD pathology is phosphorylation of Ser residues within the C-terminal part of the TDP-43 LCD, with the consensus pathological phosphorylation sites at Ser403, Ser404, and Ser409/410, and additional disease-specific phosphorylation sites at Ser379 and Ser369 3 , 38 . The full phosphorylation landscape and population of molecules phosphorylated at specific sites are, however, unknown.…”
Section: Discussionmentioning
confidence: 99%
“…One of the features of ALS and FTLD pathology is phosphorylation of Ser residues within the C-terminal part of the TDP-43 LCD, with the consensus pathological phosphorylation sites at Ser403, Ser404, and Ser409/410, and additional disease-specific phosphorylation sites at Ser379 and Ser369 3 , 38 . The full phosphorylation landscape and population of molecules phosphorylated at specific sites are, however, unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, different un-phosphorylatable mutations of Ser to Ala weakly induce phase transition. On the other hand, it is also known that phosphorylated TDP-43 represents one of the predominant components of protein aggregates in ALS and FTD ( Hasegawa et al, 2008 ; Guedes et al, 2017 ), in which TDP-43 is found phosphorylated in its LCD, mainly on Ser 403/404 and 409/410 ( Neumann et al, 2020 ). Nevertheless, whether this phosphorylation occurs before or after aggregation and its possible causative role in stabilizing protein aggregation need to be yet clarified.…”
Section: Post-translational Modifications Of Tdp-43 Fus and Hnrnp-a1 Controlling Liquid-liquid Phase Separation And Protein Aggregationmentioning
confidence: 99%
“…One of the features of ALS and FTLD pathology is phosphorylation of Ser residues within the C-terminal part of TDP-43 LCD 2,19 . Most of these phosphorylation sites are buried in the interior of the fibril structure that we determined for the non-phosphorylated protein (Extended Data Fig.…”
Section: Figmentioning
confidence: 99%